A Review of Reservoir Operation Optimisations: from Traditional Models to Metaheuristic Algorithms - Lai V.; Huang Y.F.; Koo C.H.; Ahmed A.N.; El-Shafie A. (Springer Science and Business Media B.V., 2023)
Decision making; Dynamic programming; Linear programming; Nonlinear programming; Operating costs; 'current; Energy productions; Floodings; Meta-heuristics algorithms; Optimal reservoir operations; Optimizing energy; Reservoir operation; Reservoir operation optimizations; Traditional models; Water scarcity; Reservoirs (water)